Synthesis and Characterization of Zeolite from Refractory Brick Waste - Selan, Odi Th. E.; Hema, Maria D.; Saudale, Fredy Z.; Suwari, Suwari (Universitas Nusa Cendana, 2021)
The synthesis of zeolite from refractory brick waste using hydrothermal technique had been conducted. Two different reactans, NaOH and Mg(OH)2, were separately employed to react with SiO2 and Al2O3 from brick sample to produce metal silicate and metal aluminate which were then reacted to obtain zeolite. XRF results show that the synthesized products using both reactants have Si/Al ratios between 1-1.5 considered as low type of zeolites regardless some remaining impurities. XRD data reveal a typical pattern of zeolite with 2 Ɵ angles of 15.91; 19.52; 25.47; 32.20; 35.54 and 41.54. The IR vibration characteristic of Si-O and Al-O bonds appears in 454 cm-1 while the symmetric and asymmetric stretching vibrations of these two bonds absorb around 679.66 – 778.02 cm-1 and 2033.96-1092.42 cm-1, respectively. The O-H group from Si-OH associated with the formation of zeolite gives a characteristic feature at 3618 cm-1. SEM analysis also shows similar morphological features with natrolite zeolite. The use of NaOH as reactant gives more zeolite product compared to Mg(OH)2 reactant.